EFEKTIVITAS PEMBELAJARAN PENDIDIKAN DAN PELATIHAN LATIHAN DASAR (LATSAR) MELALUI COACHING FASILITATOR P ADA BPSDMD PROVINSI NUSA TENGGARA TIMUR - P. Pieter Djoka (Jurnal Good Governance, 2018)
The year 2014 becomes a very important moment for the local government because it was published Law Number 23 Year 2014 on Regional Government. In the same year, the Government and House of Representatives (DPR) issued Law Number 5 Year 2014 on State Civil Apparatus or abbreviated ASN. In Law no. 5/2014 mentioned that ASN consists of Civil Servants (PNS) and Government Employees with Work Agreement (PPPK). In this article, the discussion is only emphasized on the management of civil servants, especially Learning Preparatory Training through Coaching Facilitator. The method of writing using qualitative methods, with data collection in the form of interviews and literature study. Based on the analysis and discussion that has been done, there are some recommendations that need to enforce the implementation of curriculum / training materials in accordance with the provisions of legislation, need to conditioning and increase the motivation of pre-service training participants to support the training objectives, need to increase the ability Widyaiswara as educators, teachers, and trainers of pre-service training, need selection and application of learning methods of pre-service training in accordance with the training materials given to the pre-service training participants, and the fulfillment of infrastructure and training facilities in order to support the successful implementation of pre-service training.Keywords: Effectiveness, Preparatory Training, Coaching Facilitator, East Nusa Tenggara.